Management of chronic scapholunate ligament injury - Wahed, Karim (J Clin Orthop Trauma, 2020)
Scapholunate ligament is the most commonly injured ligament in the wrist and requires accurate diagnosis and treatment. It presents with pain, stiffness and can lead to carpal instability as well as degenerative arthritis if left untreated, with subsequent loss of function and disability. There are several management options currently available but there is no consensus on how best to manage a wrist with chronic sequelae of scapholunate ligament injury. This review explores available evidence in the literature on optimal treatment options including non-operative and operative procedures, relevant surgical techniques and their associated outcomes. A summary of the current concepts in the management of Chronic Scapholunate ligament injury is presented.